Perceived Academic Support pada Mahasiswa Universitas Nusa Cendana - Arnol Hover Maryo Wakano; R. Pasifikus Ch. Wijaya; Rizky P. Manafe (Observasi : Jurnal Publikasi Ilmu Psikologi, 2026)
This study aimed to describe the level of Perceived Academic Support among students of Universitas Nusa Cendana. Perceived Academic Support refers to students’ perceptions of academic support received from lecturers, peers, family, and the university environment. Academic support may take the form of academic guidance, motivation, feedback, learning assistance, educational facilities, and a supportive learning environment. This research employed a quantitative descriptive approach. The participants were active students of Universitas Nusa Cendana selected through purposive sampling based on predetermined criteria. Data were collected using a Perceived Academic Support scale consisting of four dimensions: lecturer support, peer support, family support, and institutional support. Responses were measured using a five-point Likert scale. Data analysis was conducted using descriptive statistics, including minimum score, maximum score, mean, standard deviation, frequency, percentage, and category distribution. The findings indicated that most students reported a high level of Perceived Academic Support. These results suggest that students generally perceive positive academic support from their surrounding environment. The findings are expected to provide useful information for higher education institutions in strengthening academic support services and enhancing students’ learning experiences.